Geometric optimization of planar membrane reflector used in gossamer space structure. Issue 1 (December 2020) - Shinde, S. D.; Soni, M.; Upadhyay, S. H.; Sakhare, S.; Singh, K. S.
Abstract: In recent trends membrane reflector has increased its applications in space missions due its significant advantage such as light in weight, higher folding and packaging efficiency, ease of deployment, low on-Board volume requirement. Geometry of the membrane reflector has significant influence on its the stress distribution and area of deformation, subsequently determining the stiffness and geometrical parameters of its supporting structures. The present study uses a Taguchi optimization method of orthogonal array for investigating the membrane geometry parameter and its effect on membrane reflector.